Comparison of total protein and enzyme levels in successive regenerations of venom from individual coralsnakes. (July 2015) - Kopper, Randall A.; Harper, George R.; Occidental, Michael; Gamalie, Vlad; Spradley, Ples
Abstract: Coralsnakes produce highly potent neurotoxic venoms, but little is known about variations in specific enzyme components within a species or from one replenishment of venom to the next within the same animal. Since published studies are often conducted using venom pools from multiple snakes, individual differences are masked and variations among individual snakes and between subsequent venom regenerations from the same snake have rarely been documented. This study involves the analysis and comparison of four successive venom collections from each of nine individual coralsnakes in order to detect these differences. Significant variation was found within the successive re-synthesis of venom components. Even greater differences were observed between the venoms from similar individual snakes. Since studies of variation in enzymatic activity would be significant only if they were above these normal variations, it is important to be aware of these differences. These results suggest the importance of understanding the variations present within and between individuals of the same species when interpreting the potential significance of differences found as the result of genetic, environmental or ecological factors. Highlights: Coralsnake venom components vary significantly between similar individuals. Venom protein and enzyme activities vary between successive venom regenerations. Differences among individuals exceed differences in successive venom replenishments. Use of pooled venom can mask individual differences and affect interpretation of data.